Effectiveness of an improved medical care system for children in a critical care medical center: is it possible to provide an equivalent level of trauma care for children as we do for adults? - Toida, Chiaki (Acute Med Surg, 2014)
AIM: In trauma care, most events that result in preventable trauma death tend to occur in the initial phase of treatment, and providing prompt and accurate care affects the outcomes of patients with severe trauma. Developing a system for administering prompt and accurate care and encouraging team coordination is essential for children as well as adults. However, differences in physical size and vital signs specific to children are potential obstacles to carrying out physical assessments, decision‐making, procedures, and treatments in pediatric patients. An improved medical care system for children was designed at the Osaka Prefectural Senshu Critical Care Medical Center. We evaluated the effectiveness of the new system. METHODS: We enrolled all patients with severe trauma admitted to our center. The therapeutic process and outcomes of trauma care before and after the establishment of the improved system was retrospectively compared. RESULTS: The results showed a significant decline in the time required to establish an i.v. line and perform tracheal intubation before computed tomography. There were also no statistically significant differences in the timing of craniotomy or trepanation, or the time required to carry out hemostatic procedures, between children and adults. Furthermore, no patients with a probability of survival over 0.5 died following the establishment of the new system. CONCLUSION: Our newly improved medical care system facilitates treatment for children using standards equivalent to those used in adults in critical care centers, regardless of the physical size and vital signs of the patient.